Effect of finerenone on renal function in patients with type 2 diabetic nephropathy: a retrospective cohort study - Liu, Xu-Ying; Zhao, Ya-Min; Zhang, Ya-Guang; Liu, Yi; Wang, Bo-Ya; Hao, Zhen-Zhen; Hu, Man-Hui (Frontiers in Endocrinology, 2026)
BackgroundDiabetic nephropathy (DN) remains a major cause of chronic kidney disease despite optimized renin–angiotensin system blockade. This study aimed to evaluate the efficacy and safety of adding finerenone to angiotensin-converting enzyme inhibitor/angiotensin II receptor blocker (ACEI/ARB) therapy and to identify predictors of clinically meaningful renal deterioration in patients with DN.MethodsThis retrospective cohort study enrolled adult patients (18–80 years) with a confirmed diagnosis of DN according to American Diabetes Association and Kidney Disease: Improving Global Outcomes criteria, who had complete baseline and follow-up data. Patients with type 1 diabetes, non-diabetic kidney disease, severe hepatic dysfunction, advanced heart failure, recent acute cardiovascular events, or baseline hyperkalemia were excluded. A total of 240 patients treated between January 2019 and December 2024 were included. Patients receiving ACEI/ARB monotherapy (control group, n = 124) were compared with those receiving ACEI/ARB plus finerenone (observation group, n = 116). Renal and metabolic parameters were assessed at baseline and after 24 weeks. Between-group comparisons were performed using appropriate parametric or nonparametric tests, and multivariable logistic regression analysis was conducted to identify independent predictors of a ≥15% estimated glomerular filtration rate (eGFR) decline.ResultsAfter 24 weeks, patients receiving finerenone showed significantly lower Scr (128.3 ± 27.6 μmol/L vs. 140.8 ± 35.1 μmol/L, P = 0.002), higher eGFR (56.8 ± 11.4 vs. 50.1 ± 12.3 mL/min/1.73 m², P < 0.001), and lower UACR (301.4 ± 142.7 vs. 398.7 ± 176.8 mg/g, P < 0.001) than controls. Finerenone treatment independently protected against renal deterioration (adjusted odds ratio [aOR] = 0.473, 95% CI: 0.253–0.883, P = 0.019), while longer diabetes duration, lower baseline eGFR, and higher UACR predicted ≥15% eGFR decline. Both regimens were well tolerated, with no increase in severe hyperkalemia or serious adverse events.ConclusionsAdding finerenone to ACEI/ARB therapy improved renal parameters over 24 weeks and was independently associated with reduced risk of clinically meaningful eGFR decline without excess serious adverse events.